Pendampingan Siswa dalam Bidang Keterampilan dan Ekstrakurikuler di Panti Asuhan Kota Palangka Raya - Rita Rahmaniati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The problem that often occurs today is the lack of skills possessed by students. During this time students are required to excel cognitively and are less aware of the importance of having hand skills and following extracurricular activities. Through the assistance of hand skills, making crafts from simple materials can improve an independent and creative person. Through extracurricular activities of mentoring in the field of religion (call to prayer) and mentoring using Microsoft word helps students prepare themselves to face the development of science and technology very quickly, train students to communicate in writing, and be able to improve religious values. The targets in this service are children/students in the Orphanage in Palangkaraya City. Community service activities are carried out from November to December 2019 at the Ayah dan Bunda Orphanage, the Trans Kalimantan Road, and Berkah Orphanage, G.Obos XXIV. The implementation of this service received positive responses from the participants with high enthusiasm. There is still a need to do similar, more innovative service activities on an ongoing basis to shape personality according to these goals. This community service still needs to be carried out similar activities continuously to get personality according to these goals.